Tinjauan Yuridis Pemenuhan Hak Warga Binaan Narkotika Berdasarkan Undang – Undang Nomor 22 Tahun 2022 Tentang Pemasyarakatan Dirumah Tahanan Negara Kelas Iib Kota Bengkulu - Age Windri; Muhamad Calvin Yulvansyah; Aliya Perawita (GLOBAL SCIENTS PUBLISHER, 2026)
This study analyzes the regulation and implementation of the fulfillment of the rights of prisoners convicted of narcotics offenses in accordance with Law Number 22 of 2022 on Corrections at the Class IIB State Detention Center in Bengkulu City, including an evaluation of its conformity with applicable legal norms. Using a normative juridical approach and literature study, the findings indicate that the law comprehensively regulates both basic rights and integrative rights, including medical and social rehabilitation for narcotics addicts, which is integrated with Law Number 35 of 2009. However, its implementation in practice is hindered by overcrowding, inadequate infrastructure, and limited human resources. The main findings highlight a disparity between das sollen (ideal provisions) and das sein (actual conditions), thereby recommending regulatory harmonization, strengthening institutional capacity, and enhancing inter-agency collaboration to improve rehabilitation programs and social reintegration.